Lab Networks in Engineering Education: A Proposed Structure for Organizing Information - Romagnoli, Giovanni; Esposito, Giovanni; Rizzi, Antonio; Zammori, Francesco; Bertolini, Massimo; Uckelmann, Dieter (International Journal of Online and Biomedical Engineering (iJOE), 2020)
Experimentation plays an essential role in engineering education, allowing to balance theoretical proofs and emphasis on physical intuition. Laboratories can fulfil several goals at once, but they also involve high costs, mostly due to equipment, space, and human resources for operating and maintaining them. Remote-access labs have been proposed as a feasible alternative: developed since the early 2000s by an ever-increasing research community, they are real or virtual labs accessible at distance through a computer network. Recently, alternative bibliometric taxonomies and classifications of current networked remote-access labs have been proposed. Yet, none of these works proposes a comprehensive structure to collect and organize the information, especially from a technical perspective, aiming at the definition of the state of the art and future outlooks of provided solutions. In the present work, we fill this gap extending previous works by enlarging their set of criteria towards a general multi-layer model for networked remote-access labs. We performed a systematic review of relevant literature to retrieve useful information to design the structure and then validated it by using a mini-Delphi method.